The role of Iron Regulated 2 and Iron Regulated Transporter 1 in nickel hyperaccumulation traits in Senecio coronatus - Mackay, Angus (Department of Molecular and Cell Biology, 2018)
Metal hyperaccumulating plants accumulate exceptionally high concentrations of metal ions in their above ground tissues and are defined as containing 1000 μg/g dry mass Co, Cu, Cr, Pb, Zn or Ni. This is remarkable because plants typically only require small amounts of these metals for survival, such as 0.004 μg/g Ni and 15-20 μg/g Zn. Scientific investigation has sought to understand the mechanisms underpinning hyperaccumulation in order to apply them in the phyto-technological processes of phytoremediation (removal of metal pollutants from the environment) and phytomining. However, little is known about the molecular mechanisms underlying Ni hyperaccumulation despite the fact that Ni hyperaccumulators account for almost three quarters of all known hyperaccumulating species. A comparative RNA-Seq experiment carried out on Ni accumulating and non-accumulating populations of the South African Ni hyperaccumulator Senecio coronatus (Asteraceae) identified a number of putative transport proteins that are constitutively upregulated in the hyperaccumulator plants. This MSc project focused on two of these, iron regulated 2 (ScIREG2) and iron regulated transporter 1 (ScIRT1), and aimed to validate the RNA-Seq derived nucleotide sequences, test for Ni transport activity and determine their sub-cellular localisation. Full-length ScIREG2 and ScIRT1 protein coding sequences were obtained using RT-PCR and conformed to the predicted sequences derived from the RNA-Seq data. Heterologous expression of ScIRT1 in yeast consistently conferred an increased Ni resistance phenotype to yeast across a variety of experimental conditions, suggesting that this protein is capable of transporting Ni, and may function as a Ni export protein in yeast. In contrast, the results obtained from heterologous expression of ScIREG2 were variable and thus inconclusive. An attempt was made to determine the subcellular localization of ScIRT1 using transient expression of an ScIRT1-YFP fusion protein in onion cells. While inconclusive, a YFP signal was detected in these cells, and appeared to localise to the plasma membrane. The work conducted serves as a pilot study to optimize the experimental systems necessary to identify Ni transporters from S. coronatus. These experimental systems can now be applied to characterise the remaining transport proteins identified in the RNA-Seq analysis.